Louise Campbell. Une médiatrice dans l’être - Bertomeu, Fanny (Revue musicale OICRM, 2020)
Formed as a musician and a clarinetist, Louise Campbell is now a music mediator. Based in Montreal, she practices her profession through several structures and for a wide variety of audiences (schoolchildren, professionals, people with disabilities ...) all around Canada, but mainly in Quebec. In this interview, Louise Campbell recounts her experience as a mediator, her (non)-formation in this profession, as well as many aspects in her practice. With the musical object and the creation at the heart of her workshops, Louise Campbell always seeks to establish a “horizontal” exchange relationship with each person she meets.
Keywords: Louise Campbell; creation; création; music mediation; médiation de la musique; partage; relation; relationship; sharing